Entrepreneurship for Sustainability: Dampak Education Sustainability dan Awareness of Green Accounting - Julita, Julita; Desmiyawati, Desmiyawati; Natariasari, Riska; Luthfi Iznillah, Muhammad; Nabila, Kania; Izzara, Aidura (Akuntansi & Ekonomika, 2025)
This study investigates the influence of Education Sustainability on Entrepreneurship for Sustainability, moderated by Awareness of Green Accounting, among university students. The topic is critical as higher education plays a pivotal role in shaping sustainable entrepreneurial practices aligned with the Sustainable Development Goals (SDGs). Conducted at Universitas Riau, Indonesia, the research adopts a causal design with data collected via a digital questionnaire distributed to students enrolled in entrepreneurship courses. A sample of 753 respondents was selected through convenience sampling. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM), ensuring robust testing of complex models. Results reveal that Education Sustainability significantly impacts Entrepreneurship for Sustainability, with Awareness of Green Accounting functioning as both a direct predictor and a quasi-moderator. These findings emphasize the dual importance of sustainability education and green accounting awareness in fostering sustainable entrepreneurship.